(D2O–H2O) solvent isotope effects on some thermodynamic properties of the Albicar dissolution (hydration) between T = (278.15 and 313.15) K at ambient pressure. (June 2016) - Ivanov, Evgeniy V.; Batov, Dmitriy V.; Kravchenko, Angelina N.
Graphical abstract: Highlights: Enthalpies of solution of Albicar in H2 O and D2 O were measured calorimetrically. Calorimetric experiments were performed at T = (278 to 313) K and p = 99.6 kPa. Enthalpy-isotopic effect was found to be negative and decreasing with temperature. Standard molar heat capacities of solution are positive and higher in heavy water. Abstract: The molar enthalpies of solution of a drug Albicar or 1, 4-diethyl-3, 6-dimethyltetrahydroimidazo[4, 5-d]imidazole-2, 5(1 H, 3 H )-dione in ordinary (H2 O) and heavy (D2 O) water at T = (278.15, 279.15, 288.15, 298.15, 308.15, and 313.15) K and ambient pressure were measured calorimetrically. The standard (at infinite dilution) molar enthalpies and heat capacities of the solute dissolution along with the (D2 O–H2 O) solvent isotope effects (IEs) on the specified quantities were computed. The enthalpic effects of Albicar dissolution in H2 O and D2 O experience a negative-to-positive sign inversion nearby T inv = (306 and 307) K, respectively, whereas the corresponding IEs were found to be wholly negative (by sign) and decreasing in magnitude with increasing temperature. These facts indicate that the Albicar hydration, being dualistic (hydrophobic–hydrophilic) in nature, is enhanced in the D2 O medium. The hydration behavior of the studied solute was discussed in comparison with those for Mebicar (1, 3, 4, 6-tetramethyl-derivative) and Bicaret (1, 3, 4, 6-tetraethyl-derivative) using the previously obtained data.